(3GdJQHjI GdYdejI Hjf GdfXQjI h GdJWHjbs - (3GdcQOGfj eMeO aJMjs; (3eUWai GdSGjM s (((3eUQ(B)s (3OgH ddceHjhJQs, 2002)
(3d Y (B725 (3Hjf CgejI GdETQGa , GdJhLjg h GdJbhje aj GdJQHjI GdYdejI ,eJWQbG deNJda GdELQGAGJ GdafjI h GdEOGQjI h CgejJgG HGdfSHI ddWGdH GdeYde, eOYeG GdhKjbI HHYV GdfeGPL dHWGbGJ Jbhje GdWGdH GdeYde(B.s
Keywords: (3GdJQHjI GdYedjIs